2012
DOI: 10.1007/s10120-012-0173-2
|View full text |Cite
|
Sign up to set email alerts
|

“Crawling-type” adenocarcinoma of the stomach: a distinct entity preceding poorly differentiated adenocarcinoma

Abstract: Background Gastric ''crawling-type'' adenocarcinoma (CTAC) is a neoplasm histologically comprising irregularly fused glands with low-grade cellular atypia that tends to spread laterally in the mucosa. It is necessary to elucidate the clinicopathological characteristics of CTAC. Methods We evaluated 25 CTACs-16 intramucosal (M-) and 9 submucosal invasive (SM-) cancers-clinicopathologically and immunohistochemically. Results CTAC was most frequently located in the lesser curvature of the middle-third of the stom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 25 publications
4
41
0
Order By: Relevance
“…These previous studies reported some of the features that we assess here, including tortuous, branching, anastomosing, and distended glands, as well as the presence of discohesive cells. [1][2][3] A limited set of stromal features including desmoplasia and inflammation have also been noted previously. 3 The finding of 'spiky' glands, glandular outgrowth, and abortive glands as architectural features and the assessment of the remaining stromal features have not previously been described.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…These previous studies reported some of the features that we assess here, including tortuous, branching, anastomosing, and distended glands, as well as the presence of discohesive cells. [1][2][3] A limited set of stromal features including desmoplasia and inflammation have also been noted previously. 3 The finding of 'spiky' glands, glandular outgrowth, and abortive glands as architectural features and the assessment of the remaining stromal features have not previously been described.…”
Section: Discussionsupporting
confidence: 56%
“…Very well-differentiated gastric adenocarcinoma of intestinal type is a distinct variant characterized by low-grade nuclear atypia and a morphology mimicking intestinal metaplasia. [1][2][3] The neoplastic glands show subtle architectural abnormalities such as branching and anastomosis, commonly reproducing the shapes of the letters W, H, Y, or X at low power. 4 Anecdotally, we have noted the challenge in diagnosing this variant of gastric adenocarcinoma, especially on biopsy specimens, which are often misinterpreted as reactive intestinal metaplasia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, intramucosal tubular adenocarcinoma has been confirmed to have a low risk of lymph node metastasis [14,18,19] and, therefore, can be safely removed endoscopically. In histopathology, most early tubular adenocarcinomas originate in the isthmus/neck of a gastric unit along the lesser curvature in the distal stomach [13,20]. A pathologic diagnosis of early tubular adenocarcinoma requires 2 essential histology features [20,21,22]: (1) nuclear dysplastic changes with hyperchromasia, nuclear enlargement in the size of 3-4 naïve small lymphocytes, high nuclear-to-cytoplasmic ratio, marked pleomorphism, increased mitotic figures with atypical forms, prominent nucleoli, and cellular immaturity; and (2) architectural abnormalities with a spectrum of growth patterns at low power view, such as anastomosing, fusing, branching, cribriforming, budding, back-to-back crowding, microcysts, disunion, spiky glands with sharp projections, single cell clusters, abortive glands, and necrotic debris in the gland lumens.…”
Section: Diversity In the Histology Of Intramucosal Tubular Adenocarcmentioning
confidence: 99%
“…In histopathology, most early tubular adenocarcinomas originate in the isthmus/neck of a gastric unit along the lesser curvature in the distal stomach [13,20]. A pathologic diagnosis of early tubular adenocarcinoma requires 2 essential histology features [20,21,22]: (1) nuclear dysplastic changes with hyperchromasia, nuclear enlargement in the size of 3-4 naïve small lymphocytes, high nuclear-to-cytoplasmic ratio, marked pleomorphism, increased mitotic figures with atypical forms, prominent nucleoli, and cellular immaturity; and (2) architectural abnormalities with a spectrum of growth patterns at low power view, such as anastomosing, fusing, branching, cribriforming, budding, back-to-back crowding, microcysts, disunion, spiky glands with sharp projections, single cell clusters, abortive glands, and necrotic debris in the gland lumens. Recognition of the morphologic characteristics of early tubular adenocarcinoma is crucial in small biopsies to guide patient triage and management, as most patients with early tubular adenocarcinoma are treated by endoscopic, rather than surgical resection in East Asian countries.…”
Section: Diversity In the Histology Of Intramucosal Tubular Adenocarcmentioning
confidence: 99%